Detection of visual stimuli on monocular peripheral head-worn displays. (November 2018) - Pascale, Michael T.; Sanderson, Penelope; Liu, David; Mohamed, Ismail; Stigter, Nicola; Loeb, Robert G.
Abstract: Objective: To compare people's ability to detect peripherally presented stimuli on a monocular head-worn display (HWD) versus a conventional screen. Background: Visual attention capture has been systematically investigated, but not with respect to HWDs. How stimulus properties affect attention capture is likely to be different on an HWD when compared to a traditional computer display. Method: Participants performed an ongoing perceptual task and attempted to detect stimuli that were displayed peripherally on either a computer monitor or a monocular HWD. Results: Participants were less able to detect peripheral stimuli when the stimuli were presented on a HWD than when presented on a computer monitor. Moreover, the disadvantage of the HWD was more pronounced when peripheral stimuli were less distinct and when the stimuli were presented further into the periphery. Conclusion: Presenting stimuli on a monocular head-worn display reduces participants' ability to notice peripheral visual stimuli compared to presentation on a normal computer monitor. This effect increases as stimuli are presented further in the periphery, but can be ameliorated to a degree by using high-contrast stimuli. Application: The findings are useful for designers creating visual stimuli intended to capture attention when viewed on a peripherally positioned monocular head-worn display. Highlights: We examined change detection of various stimuli on real versus simulated HWDs. Visual stimuli are more difficult to detect on an HWD compared to a normal screen. The effects of eccentricity are significantly worse on an HWD compared to a screen. Increasing brightness and adding motion reduces the HWD detection disadvantage. Abstract : Factors that affect whether people notice a peripheral visual stimulus include distance of the stimulus from the primary task, stimulus brightness, and stimulus change from context. These effects are stronger when peripheral stimuli are displayed on a monocular HWD than on a computer screen.